2020
DOI: 10.3390/ijerph17114072
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Dental Caries and Malocclusion with Oral Health-Related Quality of Life in Lithuanian Adolescents Aged 15 to 18 Years: A Cross-Sectional Study

Abstract: There is a lack of evidence of the moderating effects of caries lesions and malocclusions on oral health-related quality of life (OHRQoL) among older adolescents. This study aimed to evaluate the relationship of dental caries and malocclusion with OHRQoL among Lithuanian adolescents aged 15 to 18 years. A survey in a representative sample of adolescents included a clinical examination to assess dental health status using the DMFT (Decayed, Missing, and Filled Permanent Teeth) index, and malocclusion using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…Testing has shown that it has no significant relationship with dental fear scores. Our previous study found that malocclusion, as well as caries experience, negatively affects OHRQoL [59]. The results of the present study show that a worse level of OHRQoL is associated with higher dental fear scores.…”
Section: Discussionsupporting
confidence: 55%
“…Testing has shown that it has no significant relationship with dental fear scores. Our previous study found that malocclusion, as well as caries experience, negatively affects OHRQoL [59]. The results of the present study show that a worse level of OHRQoL is associated with higher dental fear scores.…”
Section: Discussionsupporting
confidence: 55%
“…Eight of the studies were conducted in Brazil ( 20 , 36–42 ). Eight studies were conducted in school settings ( 20 , 37–43 ), three studies at schools’ dental or medical offices ( 35 , 44 , 45 ), one study at dental clinics ( 46 ), and one study in the patients’ home environments ( 36 ) ( Table 1 ). The study conducted at dental clinics ( 46 ) was the only one mentioning having access to dental radiographs for malocclusion and caries diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies used the Child Perceptions Questionnaire (CPQ) to assess OHRQoL ( 20 , 35 , 37–39 , 41 , 42 , 44–46 ). Different versions of the CPQ were used: CPQ 11-14-ISF:16 ( 20 , 38 , 39 , 41 , 42 , 44 , 46 ), CPQ 11-14-ISF:8 and RSF:8 ( 35 ), and the original CPQ 11-14 37 item questionnaire ( 37 , 45 ). One study used the Generic and Condition–Specific Child Oral Impact on Daily Performances index (Child-OIDP) ( 43 ), one the Generic OIDP ( 36 ), and one the Oral Health Impact Profile-14 (OHIP-14) ( 40 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Generic measures can capture the different quality of life elements since they include domains that are not specific to the disease condition [6] and can also represent different knowledge domains for a bothered understanding of oral health's impact on the quality of life conditions [7]. On the other hand, the specific instruments are geared towards particular health conditions that can detect special situations, such as the impact of oral diseases on children and adolescent's quality of life [8][9][10]. Quality of life measures has been widely used as a patient-reported outcome to assess the impact of health conditions on children's daily lives, providing information about the broad consequences of oral health that normative clinical indicators cannot capture [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The literature highlights the possible impact on dental caries and malocclusions in the OHRQoL study [2,9,10]. However, the health-related quality of life (HRQoL) assessment must be associated with OHRQoL, comparing the results to achieve more elaborate levels of understanding of the individual's health [6,8].…”
Section: Introductionmentioning
confidence: 99%